STUDY OF NEAR INFRARED ABSORPTION SPECTROSCOPY OF SELECTED PAIRS OF ORGANIC SOLVENTS FOR QUALITY CONTROL APPLICATIONS - Usman, M.; Hyder, M. J.; Janjua, S. A.; Aleem, M. A. (The Nucleus, 2010)
Organic solvents of various combinations & ratios, such as ethanol/commercial petrol; benzene/ethanol; toluene/commercial petrol and toluene/benzene were studied by near infrared (NIR) absorption spectroscopy. NIR spectrometer of 850–1700 nm produced distinctly separable spectral ranges for all the combinations; 1400 to 1650 nm for ethanol/commercial petrol; 1125 to 1150 nm for benzene/ethanol; 1130 to 1150 nm for toluene/commercial petrol and 1175 to 1210 nm for toluene/benzene. The calibration curves were drawn for the given pair concentrations. From the linear fitting parameters it is evident that each pair has different slope, which establishes reliability of the technique. The results revealed that each solvent in the mixture gives a clear trend of spectral region. This may be used for the analysis of mixtures of organic solvents. The technique may be utilized for the quality assurance.